Reported side effects, bother, satisfaction, and adherence in patients taking hydrocodone for non-cancer pain - Anastassopoulos, MS, Kathryn P; Chow, PharmD, Wing; Tapia, MHS, Crisanta I.; Baik, BS, Rebecca; Moskowitz, MD, Bruce; Kim, PhD, Myoung S. (Journal of Opioid Management, 2013)
Objective: Pain is a prevalent condition that often involves a neuropathic component. Hydrocodone is one of the most widely used opioids for pain but is often associated with side effects (SEs). This study sought to characterize the experience of patients taking hydrocodone for non-cancer pain. Methods: A nationwide survey of adults in the United States taking hydrocodone for non-cancer pain was conducted. The survey included questions to characterize these patients and their experience with hydrocodone-related SEs. A neuropathic pain subgroup also was examined. Results: Among 630 respondents, the average age was 50.1 years (14.25). Most (90.6 percent) were Caucasian and 72.5 percent were female. Back pain or low back pain was the most common (42.1 percent) type of pain. Almost three-fourths (73.3 percent) experienced at least one SE, and 67.3 percent reported being bothered. More than three-fourths (78.3 percent) reported being satisfied with hydrocodone relieving pain; however, less (74.8 percent) reported being satisfied with it overall. More than one-fourth (27.6 percent) reported taking hydrocodone less than instructed with 41.4 percent of them reporting that SEs were bothersome as a reason. A greater percent of the neuropathic pain subgroup (266 respondents) experienced at least one SE (80.8 percent) and were bothered by them (75.6 percent). Overall satisfaction was slightly lower (71.1 percent) among these respondents, and among the 24.8 percent taking less than instructed, more than half (54.5 percent) reported that SEs were bothersome as a reason. Conclusions: This study demonstrates an unmet need for better therapeutic options to manage pain, including neuropathic pain. Therapies that offer improved tolerability also may increase adherence, which could affect overall satisfaction and response to pain management. Keywords: hydrocodone, opioids, side effects, bother, quality of life, pain relief, patient satisfaction, adherence